Sensoriality, Art and Scenographic Culture in the 16th-18th Centuries: An interactive and Inclusive Online Exhibition - González-Román, Carmen (Mimesis Journal, 2024)
Given the importance of the digital in today's society, an online exhibition is a suitable medium for the transmission of the knowledge derived from research in the scenographic culture of the past, especially when parts of the original artistic productions were ephemeral. A consequence of this conception is the emergence of new, wide-ranging, integrating, and involving research perspectives that, based on the digital, are committed to the reconstruction of the extraordinary scenographic culture (material, sensorial, and performative) of festivals and performances during the early modern period. One of the main objectives of this virtual exhibition is to promote a participatory and inclusive experience, taking into account that users approach these artistic manifestations through a virtual space that favors interaction. The use of high-resolution images, animations, videos, and sounds is a key element of this virtual exhibition. At the same time, strategies are being planned to encourage user participation by designing their own tour or sending suggestions and materials to complement the virtual visit.